2020
DOI: 10.1111/1759-7714.13619
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin overcomes cisplatin resistance in lung cancer by inhibiting cancer cell stemness

Abstract: Background Lung cancer is the leading cause of cancer death and is commonly treated by cisplatin. Although cisplatin treatment may initially be successful, its effectiveness usually reduces significantly in disease‐recurrent patients. Aspirin, a nonselective COX inhibitor, has been shown to help reverse the status of cisplatin sensitivity in recurrent human ovarian cancer cells. This study aimed to explore the effect of aspirin on cisplatin resistance through the perspective of cancer cell stemnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Main functions of NADPH rely on variety of dehydrogenases [ 55 , 56 ]. We prove that decreased NADPH oxidase-mediated ROS may account for cisplatin resistance of NSCLC based on a published dataset [ 57 ]. Besides the maintenance of NADPH, the glutathione metabolism system is also dysregulated after APR-246 treatment.…”
Section: Discussionmentioning
confidence: 68%
“…Main functions of NADPH rely on variety of dehydrogenases [ 55 , 56 ]. We prove that decreased NADPH oxidase-mediated ROS may account for cisplatin resistance of NSCLC based on a published dataset [ 57 ]. Besides the maintenance of NADPH, the glutathione metabolism system is also dysregulated after APR-246 treatment.…”
Section: Discussionmentioning
confidence: 68%
“…Main functions of NADPH are served by a variety of dehydrogenases (48,49). We prove that decreased NADPH oxidase-mediated ROS may account for cisplatin resistance of NSCLC based on a published dataset (50). Besides to maintenance of NADPH, the glutathione metabolism system is also dysregulated after APR-246 treatment.…”
Section: Discussionmentioning
confidence: 68%
“…Further experiments in vitro showed that ASA with 4-OHT could significantly inhibit the proliferation of tamoxifen resistance cells. Studies on the reversal of drug resistance of other tumors by ASA showed that cisplatin plus ASA significantly reduced the survival rate of cisplatin-resistant tumor cells, and ASA could inhibit the expression of tumor cell-related proteins, such as ALDH1, CD44, CD133, and P53 [34,35]. ASA reduced the growth and invasion of pancreatic ductal adenocarcinoma and significantly enhanced the therapeutic effect of gemcitabine.…”
Section: Discussionmentioning
confidence: 99%